RelatÄ±onshÄ±p Among Humor Styles, Internal MarketÄ±ng PractÄ±ces And CommunÄ±catÄ±on - Ozyer, Yagmur (European Scientific Journal, ESJ, 2016)
Although humor at workplace provides positive results for the brands and intraorganizational management, there are only a few theorized studies proving this fact in the literature. Studies on humor at workplace can be mostly seen in the organizational behavior literature. Humor can be considered as a very critical component for both the internal customers and external customers in the marketing literature. Humor is effective in creating consumer perceptions and loyalty through various marketing channels and additionally, can be considered as a very important concept for maintaining the holistic marketing approach in internal marketing practices. Behaviors and attitudes of marketing department managers with different humor styles can increase cohesion among employees and maximize their performance. This study examines the effect of humor styles of the marketing department managers on the internal marketing practices under the moderating role of persuasive communication variable.